BAHAN KERING DAN BAHAN ORGANIK DAGING AYAM AKAMPUNG SUPER YANG DIBERI JERAMI JAGUNG FERMENTASI DAN BEKATUL - Sri Meilan Latabi; Ellen J.Saleh; Musrifa Nusi; Sri Suryaningsih Djunu; Haris Nur Abdul (Jambura Journal of Animal Science, 2021)
The purpose of this study was to analyze the dry matter and organic Ingredients of Kampung Super chicken which was given fermented corn straw (JJF) as a substitute for rice bran in the ration. This experimental research used a completely randomized design (CRD), with 5 treatments and 4 replications. The treatment of this research was P0 (control) = basic ration containing 20% bran., P1 = basic ration containing 15% bran + 5% JJF., P2 = basic ration containing 10% bran + 10% JJF., P3 = basic ration containing 5% bran + 15% JJF., P4 = basic ration contains 20% JJF. The parameters observed were the dry matter and organic matter content of Kampung Super chicken. Analysis of variance was used for data analysis. The results showed that the addition of JJF did not affect (P 0.05) the dry matter and organic matter content of Kampung Super chicken meat. Fermented corn straw as a substitute for rice bran up to 20% in the ration does not have a significant effect on dry matter and organic matter of super native chicken meat and can be used as a substitute for bran in the ration.